PRIMA: A Proposed Teacher Development Program Focused on Expanded Career Progression System (ECPS) - Santidad, Judy Marie; Edna Manaig; Fernando Pendon III (Researchparks Publishing, 2025)
This study titled ”PRIMA: A Proposed Teacher Development Program Focused on Expanded Career Progression System (ECPS)” aimed to assess the level of awareness and preparedness of teachers towards Expanded Career Progression System among the public elementary schools in the Division of Cabuyao during the School-Year 2024-2025. This descriptive-correlational research involved the teachers of the public elementary schools in the division of Cabuyao who have been identified through the stratified sampling technique utilized by the researcher. The prime source of data are the survey-questionnaires that have been administered among the respondents. The data were used to described the level of awareness of teachers towards the Expanded Career Progression System (ECPS). It was also used to determine the level of preparedness of teachers towards the ECPS. The data collected were treated by the statistical tools appropriate to the study. The study revealed that the teachers involved in the study are mostly mid-adults who are with balanced energy and experience on their roles. The teaching profession remains female-dominated which reflect the ongoing gender trends. Most of the teachers have pursued advanced studies and possess significant teaching experience. The teachers have demonstrated strong awareness and preparedness across all components of the ECPS, specifically in competency-based promotion, position classification, tenure, leadership roles, and external recognition. The teachers’ understanding manifests a well-informed workforce, though further support is still needed to enhance their preparedness to the specific areas. Preparedness does not significantly different when grouped according to their sex and age, but difference based on their highest educational attainment and length of service claim that professional background influences how the teachers engage themselves to ECPS. Additionally, the teachers with higher level of awareness tend to make them feel more prepared which underscores the vital role of information in shaping career advancement. The Teacher Development Program is grounded to these significant findings, is expected to ameliorate both the level of awareness and preparedness and equip the teachers with the competencies needed for their future roles.